São Pedro: foreiros ou arrendatários?: a lei e a experiência social na formação urbana da cidade de Itabuna (1967-2002) - Santos, Eduardo Antonio Estevam (2009)
This dissertation analyzes the narratives of subjects who printed a different meaning to the juridical contract that established the legal conditions for possession and housing. The meanings and experiences of social life were analyzed from the cultural studies perspective, historiographic current heterogeneous in their approaches, but it focused on the subject the senses of their actions rather than it structures. It has its initial goal in 1967 when was created the São Pedro settlement and the first occupations, and outcome in 2002, when, by the first time, the association of people organized a seminar to discuss the end of Renting. Within the framework of urban illegality, these individuals built their homes, provided the area of social significance and gave the steps to urbanize the district. This study also discusses the power and limits of the law against the political action of private agents and public power which is the official laws formulator and arbiter of the land conflicts. Through oral history, it articulates impressions, interpretations and meanings of Renting on the experience of housing and the constitution of the São Pedro district. It also examines the importance of oral history as an instrument of change, since the oral parts were essential to the decrees publication that banned the collection of the forum